2013
DOI: 10.1186/1556-276x-8-469
|View full text |Cite
|
Sign up to set email alerts
|

Dirac cone in α-graphdiyne: a first-principles study

Abstract: We investigate the Dirac cone in α-graphdiyne, which is a predicted flat one-atom-thick allotrope of carbon using first-principles calculations. α-graphdiyne is derived from graphene where two acetylenic linkages (-C ≡C-) are inserted into the single bonds (-C-C-). Thus, α-graphdiyne possesses a larger lattice constant which subsequently affects its electronic properties. Band structures show that α-graphdiyne exhibits similar Dirac points and cone to graphene. Further, the tight-binding method is used to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…To this end, many other 2D materials are explored theoretically and experimentally. [11][12][13][14][15][16] A search for an intrinsic band gap is prerequisite to allow the efficient control of carriers by external field.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, many other 2D materials are explored theoretically and experimentally. [11][12][13][14][15][16] A search for an intrinsic band gap is prerequisite to allow the efficient control of carriers by external field.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Apart from that, four main types of graphynes have been proposed and identified, α-Graphynes, β-graphyne, γ-graphyne and 6,6,12-graphyne, 16,22 each with different percentage of acetylenic linkages. Previous first-principle calculations [22][23][24][25] have shown that α-Graphynes, β-graphyne and 6,6,12-graphyne possess Dirac cone-like band strictures at the Fermi level. 22,26,27 Regardless of the absence of the hexagonal (p6m) symmetry, 6,6,12-graphyne exhibits high carrier mobility like graphene.…”
Section: Introductionmentioning
confidence: 98%
“…6 Among all these 2D allotropes, the Dirac cone materials attract more attentions because of its extraordinary electrical properties. From 2012, a series of 2D carbon allotropes with Dirac cones were predicted using the rst principle methods, such as a-graphdiyne, 7 a-, b-, and 6,6,12-graphyne, 8 14,14,14graphyne and 14,14,18-graphyne, 9 S-, D-, and E-graphene, 10 phagraphene, 11 and a-2 graphyne. 12 However, most of these allotropes are much unstable in thermodynamics so that their possible preparations and potential applications are greatly limited in experiment.…”
Section: Introductionmentioning
confidence: 99%